2010
DOI: 10.1097/cji.0b013e3181c01fcb
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tumor Eradication by Combining CTLA-4 or PD-1 Blockade With CpG Therapy

Abstract: Tumor immunotherapy aims to break effector T-cell anergy and to block suppressive cell types and ligands allowing effector cells to exert tumor eradication. Previous reports demonstrate that cytotoxic T lymphocyte antigen-4 (CTLA-4)-blocking antibodies promote T-cell activation and render T effector cells resistant to T regulatory cells (Tregs) whereas programmed death receptor-1 (PD-1)/PD-L1 blockade results in loss of peripheral tolerance. Herein, we explored single or combined antibody blockade of CTLA-4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(122 citation statements)
references
References 40 publications
3
117
1
1
Order By: Relevance
“…Radical cystectomy for patients with muscle-invasive bladder cancer results in initial tumor control, but provides a 5-year survival rate of only 40% to 60% due to the presence of micrometastatic disease (2). We have previously shown that local adenoviral CD40L (AdCD40L) as well as CpG therapy can induce systemic antitumor responses in experimental bladder cancer (5,6). AdCD40L therapy has proven efficient and safe in both humans (7) and dogs (8).…”
Section: Introductionmentioning
confidence: 99%
“…Radical cystectomy for patients with muscle-invasive bladder cancer results in initial tumor control, but provides a 5-year survival rate of only 40% to 60% due to the presence of micrometastatic disease (2). We have previously shown that local adenoviral CD40L (AdCD40L) as well as CpG therapy can induce systemic antitumor responses in experimental bladder cancer (5,6). AdCD40L therapy has proven efficient and safe in both humans (7) and dogs (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, other reports show that the therapeutic improvements are modest [80] and in some cases restricted to antigen presentation in the context of minor histocompatibility complexes [63]. In most of the experimental systems and clinical trials, PD-L1/PD-1 blockade works best in combination with other immune-stimulatory approaches, or even chemotherapy [62,64,81,82]. Even though PD-L1/PD-1 blockade may in fact lead to inflammatory responses (Table 1), we propose that reinforcing T cell differentiation by providing strong signals three will certainly improve PD-L1/PD-1 blocking as an effective therapeutic strategy.…”
Section: Application Of Pd-l1/pd-1 Blockade In Clinical Trialsmentioning
confidence: 99%
“…Thus, its blockade augments anti-cancer immune responses and improves immunotherapy [59,60]. However, in many instances PD-L1/PD-1 blockade or silencing using siRNA results in limited therapeutic activities, unless given in combination with other treatments such as co-administration with anti-CTLA4 antibodies [61,62], PD-L2-blocking antibodies [63], TLR ligands [62], chemotherapy [64], cytokine treatments [65] or modulators of intracellular signalling pathways in DCs [39]. It is yet unclear why PD-L1/PD-1 blockade on its own does not achieve optimal therapeutic effects in these experimental models.…”
Section: Pd-1/pd-l1 Negative Co-stimulation and Its Role In T Cell Acmentioning
confidence: 99%
“…Antibodies able to block PD-L1 and CTLA-4 administered intratumorally improves long-term survival and leads to increased levels of tumor-reactive T cells and decreased numbers of Tregs at the tumor site. Therefore, this experimental model has allowed an approach to the understanding of immune suppression during immune therapy with BCG and represents a new therapeutic option in the treatment of bladder cancer (Mangsbo et al, 2010).…”
Section: Immunotherapymentioning
confidence: 99%